Carbon sequestration potential of conservation agriculture in the CWANA region - Kaur, Ranjeet; Das, Bappa; Mondal, Surajit; Chakraborty, Debashis (International Maize and Wheat Improvement Center, 2023)
The CWANA (Central and West Asia and North Africa) region was once considered the birthplace of civilizations and played a significant role in sustaining ancient empires like the Romans through its agricultural productivity. The area is characterized by diverse agroclimatic conditions, which vary across the countries in this extensive region in terms of climate, soil, and topography. Agriculture continues to make a significant contribution to the GDP of many CWANA countries, creating job opportunities and ensuring food security. However, the region faces challenges such as water management issues, land degradation, and vulnerability to climate change. In recent years, Central and West Asia and North Africa (CWANA) have become a climate hotspot due to drought and warming, exacerbating challenges in the world's most water-stressed and socially fragile region (Schilling et al., 2020; Stewart et al., 2007; Ryan et al., 2006). Agriculture and water are the region's critical vulnerabilities.